Early Life Stress Effects on Glucocorticoid—BDNF Interplay in the Hippocampus - Daskalakis, Nikolaos P.; De Kloet, Edo Ronald; Yehuda, Rachel; Malaspina, Dolores; Kranz, Thorsten M. (Frontiers in Molecular Neuroscience, 2015)
Early life stress (ELS) is implicated in the etiology of multiple psychiatric disorders. Important biological effects of ELS are manifested in stress-susceptible regions of the hippocampus and are partially mediated by long-term effects on glucocorticoid and/or neurotrophin signaling pathways. Glucocorticoid (GC) signaling mediates the regulation of the stress response to maintain homeostasis, while neurotrophin signaling plays a key role in neuronal outgrowth and is crucial for axonal guidance and synaptic integrity. The neurotrophin and glucocorticoid signaling pathways co-exist throughout the central nervous system (CNS), particularly in the hippocampus, which has high expression of glucocorticoid and mineralocorticoid receptors (GR and MR) as well as brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase receptor B (TrkB). This review addresses the effects of ELS paradigms on GC- and BDNF- dependent mechanisms and their crosstalk in the hippocampus, including potential implications for the pathogenesis of common stress-related disorders.